Analysis on the use of a new explosive and geological condition with a mine-to-mill approach for a limestone quarry located in the vicinity of Madrid, Spain - Gurrea Matus, Gabriel Ismael (2024)
The main objective of this work is the analysis of the use of a new explosive and geological condition with a mine-to-mill approach for limestone in Valdilecha, Spain. Initially, a general description of the mine site is provided, where the focus is on the unitary process: Drill & Blast, Load & Hauling, and Processing stage. A group of 15 blasts is analyzed, and of these several KPIs are defined to create a Base Line for the quarry. Then this information is contrasted with data gathered collected by the team and is processed using different tools, through this is possible to contrast the data and evaluate the use of different technologies. Then, the impact of a new explosive is evaluated on 3 blasts. Through this, a New Design scenario allows a comparison between downstream process KPIs. Finally, the drill-to-mill approach seeks to digitally integrate the processes of drilling, blasting, loading, transport, and processing in the plant. It is expected that the information collected will allow the modeling of different scenarios and study their impact on the main production indicators, becoming a decision support tool for the management and administration of the daily operation of the quarry.
no embargo
Keywords: Mine to Mill; Mine Digitalization; Bergbau; Digitalisierung